THE SIGNIFICANCE OF PREJUDICIAL CIRCUMSTANCES IN INTERNATIONAL COOPERATION IN THE FIELD OF CRIMINAL LEGAL PROCEEDINGS - Suyunova Dilbar Joldasbaevna, (Scholar Express Journals, 2022)
The article analyzes the essence and features of the application of the institution of prejudice in criminal proceedings in some countries, examines the opinions of scientists on the procedure for the implementation of prejudice, makes some judgments on the use of prejudice in the provision of legal assistance in international cooperation.
Keywords: Legal proceedings; prejudice; implementation of prejudic; proof